A Climate Club as a complementary design to the UN Paris agreement. Issue 1 (2nd January 2020) - Pihl, Håkan
Abstract: The global coverage and the need for consensus explain why the UN Paris agreement, in several critical dimensions, is characterized by low levels of commitment and reciprocity. Hence, complementary designs are needed. This paper analyzes the parameters of such designs. New agreements should cover only nations that are willing to high levels of commitments and reciprocity. They should use measures that governments can control and be made accountable for. Commitments should be short-term and few-dimensional and they should incentivize efficient reductions, prevent leakages to outside nations and provide sanctions for noncompliance. Further, they should provide incentives to outsiders to reduce emissions and encourage them to join the agreement. A Climate Club that harmonizes minimum national carbon prices (i.e. carbon taxes), introduces a common carbon tariff, and welcomes new members to meet these criteria. Such a complementary design also has the potential to expand and, with time, provide a global price on carbon. Policy relevance: The paper demonstrates the need to develop complementary international climate policies to the Paris agreement. It analyzes design flaws of the UN agreements and, as a complement, proposes a Climate Club among nations that are willing to introduce a price on carbon. By agreeing on a carbon tax and a carbon tariff, the club creates mechanisms that reduce emissions and enlarge the club, with the potential to provide a global price on carbon. Policy insight: The Paris design includes all nations. Such a design will be insufficient. Nations with low ambitions are provided with a veto-right, which explains the flaws of the Paris agreements. A complementary design among nations with high ambitions is needed to compensate for the flaws of the Paris agreement. By agreeing to an internal minimum carbon price and an external carbon tariff, a Climate Club can create such a design.